Gambaran Kecemasan Pada Peksos dalam Mendampingi Anak Berhadapan dengan Hukum di Dinas Sosial Kabupaten Lima Puluh Kota - Muhammad Ilham; Desmita Desmita; Wahidah Fitriani; Sisrazeni Sisrazeni (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2022)
This study aims to determine the anxiety of social workers, to determine the type of anxiety in social workers in assisting ABH. This type of research is descriptive qualitative research. The results of the author's research found that: 1) the description of anxiety in social workers in assisting children in dealing with the law found that one social worker in the social service office in fifty cities with the initials AA had three aspects of anxiety, namely behavioral aspects, cognitive aspects and magical aspects. Social workers with the initial Y only have one aspect of anxiety, namely the behavioral aspect. 2) the type or form of anxiety for social workers in assisting children in dealing with the law, it was found that one social worker at the social service office in fifty cities had a type of social worker anxiety with the initial Y having mild anxiety.